2003
DOI: 10.1038/sj.bjc.6600744
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographically-guided fine-needle aspiration of axillary lymph nodes: role in breast cancer management

Abstract: The knowledge of the status of axillary lymph nodes (LN) of patients with breast cancer is a fundamental prerequisite in the therapeutic decision. In the present work, we evaluated the impact of fine-needle aspiration cytology (FNAC) of ultrasonographically (US) selected axillary LN in the diagnosis of LN metastases and subsequently in the treatment of patients with breast cancer. Axillary US was performed in 298 patients with diagnosed breast cancer (267 invasive carcinomas and 31 ductal carcinoma in situ DCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
4
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(143 citation statements)
references
References 27 publications
4
124
4
8
Order By: Relevance
“…The discrepancy in that case is explained by the fact the patient was treated with neoadjuvant chemotherapy before the full lymph node dissection was performed and scarring was identified on the histologic section of 1 of the lymph nodes, presumably corresponding to a 'burnt-out' focus of metastatic carcinoma. Although some studies also report an absence of false-positive cases, 13,14 others have reported falsepositive rates of 1.4% to 1.6%. 7,11 Conclusions FNA is a sensitive and very specific method with which to detect metastases in the axillary lymph nodes of patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The discrepancy in that case is explained by the fact the patient was treated with neoadjuvant chemotherapy before the full lymph node dissection was performed and scarring was identified on the histologic section of 1 of the lymph nodes, presumably corresponding to a 'burnt-out' focus of metastatic carcinoma. Although some studies also report an absence of false-positive cases, 13,14 others have reported falsepositive rates of 1.4% to 1.6%. 7,11 Conclusions FNA is a sensitive and very specific method with which to detect metastases in the axillary lymph nodes of patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…9 To improve the accuracy of the preoperative assessment of axillary lymph nodes, others have used FNA and found it to be simple, moderately accurate, and minimally invasive, and a good triage tool for the management of patients. 1,[7][8][9][10][11][12][13]15,19 Indeed, it has been shown that combining axillary ultrasonography with FNA cytology of abnormal lymph nodes can significantly reduce the number of unnecessary sentinel lymph node procedures performed by 8% to 40%, with a concomitant reduction in healthcare costs of up to 20%. [7][8][9][10]15,19 The data from the current study confirm that FNA cytology is a useful procedure with which to detect axillary lymph node metastases from breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, 44 articles included information relating FNAC and breast cancer diagnosis. But only 21 of 44 articles satisfied the requirements of the meta-analysis fully (Bonnema et al, 1997;Bedrosian et al, 2003;Deurloo et al, 2003;Kuenen-Boumeester et al, 2003;Sapino et al, 2003;Duchesne et al, 2005;Podkrajsek et al, 2005;Popli et al, 2006;van Rijk et al, 2006;Altomare et al, 2007;Ciatto et al, 2007;Alkuwari et al, 2008;Tahir et al, 2008;Baruah et al, 2010;Jung et al, 2010;Luparia et al, 2010;Carroll et al, 2011;Devaraj et al, 2011;Hayes et al, 2011;Schiettecatte et al, 2011), addressing the value of FNAC in staging of axillary lymph node in breast cancer patients. The detailed procedure was seen in Figure 1.…”
Section: Literature Search and Selectionmentioning
confidence: 99%
“…By contrast, using US-guided FNA, certain authors have demonstrated a sensitivity and specificity ranging from 42. (20)(21)(22)(23)(24)(25)(26)(27)(28). US-guided FNA has a high accuracy rate (5,7).…”
Section: Introductionmentioning
confidence: 99%